Is post hysterectomy adnexal torsion a complication of laparoscopic approach? A retrospective cohort study. (September 2019) - Ravid, Eyal; Klein, Zvi; Arbib, Nissim; Sharvit, Merav; Josephy, Dana; Schonman, Ron
Abstract: Objective: To investigate the correlation between the hysterectomy's surgical approach and post hysterectomy adnexal torsion. Study design: Retrospective cohort study of patients with diagnosed adnexal torsion after hysterectomy (abdominal, vaginal and laparoscopic approaches) in a tertiary care medical center from 2007 through 2017 was done. Demographic data, clinical symptoms, type of previous hysterectomy, surgical findings and treatment were retrospectively reviewed from patient records. To calculate the risk of post-hysterectomy adnexal torsion (PHAH) and evaluate its association with type of hysterectomy, we used a national hysterectomy registry that included all hysterectomy done in region of our medical centre. Results: Eight cases of AT after hysterectomy were operated during the study period, seven after laparoscopic and one after vaginal hysterectomy. Torsion occurred a mean of 27.25 ± 16.65 months (range 3–60 months) after surgery. Mean patient age at AT was 45 ± 4.6 years. All patients presented with abdominal pain, five (62.5%) had nausea and vomiting and one had diarrhoea. Laparoscopic findings revealed ovarian torsion in 5 cases, fallopian tube torsion in one and torsion of the adnexa in two cases. The national hysterectomy registry in the geographic region of our hospital summarized 705 patients with laparoscopic hysterectomy with adnexal preservation. The prevalence of post-laparoscopic hysterectomy adnexal torsion was significant high than after other types of hysterectomy (P < 0.05). Conclusion: PHAT occurs more frequently after laparoscopic hysterectomy then after other approaches. Measures for prevention of adnexal torsion should be considered during the primary surgery.